Proceso de atención de enfermería en lactante menor con neumonía en el área de pediatría del Hospital Sagrado Corazón de Jesús - Villalta Crespo, Odalis Rosicela (2020)
The Nursing Care Process that presents a continuation has as its main objective to identify the altered needs, correct, maintain and rehabilitate the patient through the application of knowledge and procedures, with the determination that this will be recovered in less time as possible your health, in this case a minor infant with pneumonia. Today, pneumonia is the leading cause of death of children under 5 years of age worldwide, its main involvement is the pulmonary alveoli, which compromises the respiratory pattern. This disease, if not treated in a timely manner, may have complications such as: acute respiratory failure, lung abscess, congestive heart failure. Priority needs were identified based on the assessment of Marjory Gordon's 11 functional patterns; An individualized care plan was designed, and for this it is used in the taxonomies: NANDA, NOC and NIC.